Pengaruh Audit Syariah dan Kualitas Layanan terhadap Kepercayaan Masyarakat pada Lembaga Amil Zakat - Aprilia Geriyam Cristanti; Nasywa Aininda Rohmawati; Devi Ashari; Tifa Asyifa Khoeriyah; Denada Rahmawati; Herlina Manurung (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
The Amil Zakat Institution plays a crucial role in distributing the blessings of wealth to people in need in line with sharia principles. For this institution, ensuring transparency and accountability in the management of zakat funds is a must. Therefore, sharia audits and service quality are important aspects that influence public trust in this institution. This research will focus on the influence of sharia audits and service quality on public trust in zakat amil institutions, with a case study at Yatim Mandiri. This research is a library study using descriptive analysis. The source of analysis used is previous research which is then compared with theories related to sharia revision. Each Mandiri has a special program to report the collection and distribution of available ZIS funds. Accountability is not only expressed in financial reports but can also be stated in the organization's agenda. Good work program coordination is expected to guarantee the effectiveness of the work program thereby bringing achievements to the school. In its understanding, sharia audit is a process to ensure that activities carried out by sharia financial institutions do not violate sharia or to comprehensively examine sharia compliance with sharia bank activities. The discussion in this research focuses on the amil zakat organization, namely LAZ YATIM MANDIRI. The implementation of the sharia audit at LAZ YATIM MANDIRI focuses on transparency and the use of funds from the community which cannot be audited due to the complicated dualism of YM management.